Acute Pressor Response to Psychosocial Stress Is Dependent on Endothelium‐Derived Endothelin‐1. Issue 4 (16th February 2018) - Fox, Brandon M.; Becker, Bryan K.; Loria, Analia S.; Hyndman, Kelly A.; Jin, Chunhua; Clark, Hannah; Johns, Robin; Yanagisawa, Masashi; Pollock, David M.; Pollock, Jennifer S.
Abstract : Background: Acute psychosocial stress provokes increases in circulating endothelin‐1 (ET‐1) levels in humans and animal models. However, key questions about the physiological function and cellular source of stress‐induced ET‐1 remain unanswered. We hypothesized that endothelium‐derived ET‐1 contributes to the acute pressor response to stress via activation of the endothelin A receptor. Methods and Results: Adult male vascular endothelium‐specific ET‐1 knockout mice and control mice that were homozygous for the floxed allele were exposed to acute psychosocial stress in the form of cage switch stress (CSS), with blood pressure measured by telemetry. An acute pressor response was elicited by CSS in both genotypes; however, this response was significantly blunted in vascular endothelium‐specific ET‐1 knockout mice compared with control mice that were homozygous for the floxed allele. In mice pretreated for 3 days with the endothelin A antagonist, ABT‐627, or the dual endothelin A/B receptor antagonist, A‐182086, the pressor response to CSS was similar between genotypes. CSS significantly increased plasma ET‐1 levels in control mice that were homozygous for the floxed allele. CSS failed to elicit an increase in plasma ET‐1 in vascular endothelium‐specific ET‐1 knockout mice. Telemetry frequency domain analyses suggested similar autonomic responses to stress between genotypes, and isolated resistance arteries demonstrated similar sensitivity to α1 ‐adrenergic receptor‐mediated vasoconstriction. Conclusions: These findings specify that acute stress‐induced activation of endothelium‐derived ET‐1 and subsequent endothelin A receptor activation is a novel mediator of the blood pressure response to acute psychosocial stress.